Comorbidities and relevant outcomes, commonly associated with cancer, of patients newly diagnosed with advanced non‐small‐cell lung cancer in Sweden. (2nd October 2019) - Linden, Stephan; Redig, Josefine; Banos Hernaez, Ana; Nilsson, Jonas; Bartels, Dorthee B.; Justo, Nahila
Abstract: Objective: The objective was to describe the prevalence of baseline comorbidities in patients with advanced NSCLC and the incidence rate of relevant outcomes commonly associated with NSCLC, and its treatments, in the year after diagnosis. Methods: A non‐interventional cohort study compared adult patients newly diagnosed with advanced NSCLC during 2006–2013 with the general population. The prevalence of comorbidities one year before and incidence of relevant outcomes one year after NSCLC diagnosis were informed by data on all healthcare visits from two large regional registers. Main summary measures were prevalence, median survival, odds ratios (ORs), incidence rate (IR) and mortality rate (MR) with corresponding 95% confidence intervals (CIs). Results: A total of 3, 834 NSCLC patients were matched to 15, 332 comparators. The prevalence of analysed comorbidities was significantly higher for NSCLC patients compared to the general population, with an OR of 2.44 (95% CI 2.27–2.63). Overall, the majority of IRs were higher for NSCLC patients, compared to the general population. The all‐cause MR for the NSCLC cohort was significantly higher leading to an IR ratio of 32.5 (95% CI 31.0–34.2). Conclusions: Advanced NSCLC patients presented with significantly more comorbidities in the year before diagnosis and relevant outcomes of interest in the year after.